As políticas para o Ensino Superior no governo Lula (2003 – 2010): análise dos pesquisadores - Vaz, Suzanete Aparecida de Freitas (2017)
The research in question has as its focus the investigation the educational policies in Higher Education elaborated during the period of the government Luiz Inácio Lula da Silva (2003 – 2010). We aim to analyze how educational policies were implemented in Higher Education in the administration of government Luiz Inácio Lula da Silva, what were the main advances, difficulties and challenges of this government in higher education, particularly with regard to FIES and PROUNI. To achieve our goal during the research, we carry out the following course: in the introduction we deal with our research object, we present the State of Art methodology, according to Romanowski (2006) and how we organize our work. In the first chapter we began the discussion on State Reform in the 1990s and the implementation of neoliberal policies in the country; from these assumptions we analyze how social policies (economic, educational, health, etc.) have been adjusted by the governments since the 1990s, consequently what the implications of these policies for Higher Education. In the second chapter, we highlight the policies that marked the administration of the Luiz Inácio Lula da Silva government (2003 – 2010) for Higher Education, emphasizing the FIES and PROUNI programs, in order to understand the influence of the multilateral organizations in the elaboration of the reform of Higher Education in this period. In the third chapter we analyze the researches about the implementation of programs for Higher Education during the Lula administration, which enabled us to list the following categories: Expansion, privatization and democratization, which allowed us to analyze the progress, difficulties and challenges of the Lula administration during the years 2003-2010 according to the authors analyzed. We conclude that the management of the Lula government for Higher Education did not break with the demand of the neoliberal policies developed in the country since the 1990s.